Khasiat Buah Manggis Untuk Kehidupan - Syakir, Darmawansyih (Al-Hikmah Journal for Religious Studies, 2014)
Mangosteen (Garcinia mangostana) is the fruits with all special quality and better than other fruits. It is not only its flesh but also its mangosteen skin is rich of essence which is beneficial to the bodily health. Â It is such as xanthone essence, antosianin essence which is categorized as antioxidant. The antioxidant of xanthone which can be found in mangosteen skin is much more than other fruits.